EphrinB–EphB signaling regulates spinal pain processing via PKCγ. (29th October 2015) - Zhou, X.-L.; Zhang, C.-J.; Wang, Y.; Wang, M.; Sun, L.-H.; Yu, L.-N.; Cao, J.-L.; Yan, M.
Highlights: EphrinB2-Fc caused PKCγ activation. Knockdown of PKCγ prevented pain induced by ephrinB2-Fc. EphB2-Fc reduced PKCγ activation in pain models. Abstract: Spinal ephrinB–EphB signaling is involved in the modulation of pain processing. The aim of the present study was to investigate whether protein kinase C-γ (PKCγ) acts as a downstream effector in regulating spinal pain processing associated with ephrinB–EphB signaling in mice. The intrathecal injection of ephrinB2-Fc, an EphB receptor activator, caused thermal hyperalgesia and mechanical allodynia, as well as increased activation of spinal PKCγ. Knockdown of spinal PKCγ prevented the pain behaviors induced by ephrinB2-Fc. Furthermore, the intrathecal injection of EphB2-Fc, an EphB receptor blocker, suppressed formalin-induced inflammatory, chronic constriction injury (CCI)-induced neuropathic, and tibia bone cavity tumor cell implantation (TCI)-induced bone cancer pain behaviors, in addition to reducing the activation of spinal PKCγ. Finally, the intrathecal injection of MK801, an N -methyl-d -aspartate (NMDA) receptor blocker, prevented the pain behaviors and spinal PKCγ activation induced by ephrinB2-Fc. Overall, the results confirm the important role of PKCγ in the regulation of spinal pain processing associated with ephrinB–EphB signaling.